HUBUNGAN SIKAP DENGAN PRESTASI BELAJAR YANG DICAPAI OLEH MAHASISWA SEMESTER IV PADA MATA KULIAH ASUHAN KEBIDANAN II Di Akademi Kebidanan Muhammadiyah Madiun: Relationship Attitude To Learning Outcome Achieved by Semester IV Students In Midwife Care II At the Muhammadiyah Madiun Midwifery Academy - Lilis Suryani (LPPM - STIKES Pemkab Jombang, 2019)
Learning achievement is the result of the assessment of teachers learning from students' learning outcomes in accordance with the instructional objectives regarding the content and behavior expected of students. Positive learning attitude will lead to higher activity compared with a negative attitude. If other factors being equal, a positive learning attitude of students will learn more active and thus will obtain better results in comparison with the negative learning attitudes of students, when studying at college can not change the insights and academic or social behavior when students graduate from college, they just grow or title attribute. The purpose of research to determine the relationship of attitudes to the achievement of students in the fourth semester of Midwifery Care II Lecture at the Academy of Midwifery Muhammadiyah Madiun. The research includes studies using associative croos sectional approach with a population of IV semester students Muhammadiyah Midwifery Academy of Madiun dated July 2, 2017. The variables used are independent variables with two pairs of samples that is the attitude of student learning and achievement. The population of 46 respondents using sampling techniques saturated. Collecting data using questionnaires, were analyzed using the Spearman Rank test statistics with significant levels of 0,05. Spearman Rank test results obtained t count = 39.22> t table = 2.021, meaning that there is a relationship between attitudes with student learning achievement at the fourth semester II Courses at the Academy of Midwifery Care Midwifery Muhammadiyah Madiun. See research result, need cooperation existence either from entire civitas academic person, good student university, lecturer, environment, with tool and infrastructure that subsidize. Creativity and innovation in will submit also praktikum in laboratory will evoke attitude will learn good, so that will increase accomplishment will learn in Midwifery Care